THE ADHERENCE TO FIXED-DOSE COMBINATION ANTIRETROVIRAL THERAPY AND VIRAL LOAD IN HIV PATIENTS - Auliannissa, Salma; Bustamam, Nurfitri; Ningsih, Sri Rahayu (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Antiretroviral fixed-dose combination (FDC ARV) has been used in HIV patient therapy. The therapy is recommended to be monitored using a viral load (VL), reflecting the amount of HIV in the blood. Since 2015, the VL testing has been carried out at Pengayoman Cipinang Hospital. However, the evaluation of adherence to the FDC antiretroviral therapy on VL has never been conducted. This study aims to determine the relationship between the adherence level to the FDC ARVs and VL at Pengayoman Cipinang Hospital in 2015-2018. The study used a cross-sectional design and a random sampling technique. The sample size was 70, and data generated from the medical record. Kruskal Wallis test showed no differences in the level of adherence in the group based on gender, education level, marital status, employment status, and the risk factor for HIV. However, there was a significant difference in the age group. Cross-tab data showed virological failure (VL> 400 copies/ml) was found in 1.8% of patients with good adherence, 75% of patients with moderate adherence, and 100% of patients with poor adherence. The Chi-square test showed a significant relationship between adherence to FDC ARV and VL (p=0.000). It can be concluded that there was a significant relationship between the level of adherence in taking ARV FDC and viral load.